Exploring Artificial Intelligence Role in Enhancing Medical Education for Future Physicians: Artificial Intelligence Role in Medical Education - Din, Mohi Ud; Ali, Muhammad; Saira, .; Naeem, Ifra; Mahmood, Ayman; Raza, Ali (Pakistan Journal of Health Sciences, 2025)
Artificial intelligence (AI) has the potential to completely transform medical education by improving learning outcomes through data-driven insights, simulation, and individualized instruction. Objectives: To determine the impact of Artificial Intelligence on Medical Education and medical students' willingness and readiness to use it. Methods: An analytical cross-sectional study was conducted among medical students at a private medical institute. Ethical approval and informed consent were taken. The questionnaire was distributed through social media platforms. Mann-Whitney U test was performed, mean + SD was taken and Pearson correlation was used to assess mean rank distributions, higher means among variables, and significant associations. A p-value of <0.05 was considered statistically significant. Results: Higher mean ranks by the Mann-Whitney U test in all perception-related questions indicated a tendency for higher values in males than females. The mean + SD of perception score was 3.63 ± 0.66 and the willingness was 3.48 + 0.69 which showed a positive perception and willingness to use AI. ANOVA was employed with the most significant association, enabling doctors to make correct decisions. Pearson correlation between readiness for AI and their perceptions, and willingness to use AI showed a strong positive correlation between them with p values significant at <0.01 level. Conclusions: It was concluded that AI could revolutionize medical education by enhancing learning, and clinical decision-making, and supplementing traditional teaching methods. A significant positive correlation was found between AI readiness, perceptions, and willingness to use it, recognizing its role in shaping future medical practice.